Temporary arrest of root development in a premolar of a child with hypodontia and extensive caries - S. T. MCDONNELL, H. LIVERSIDGE, & M. KINIRONS (Paediatric Dentistry, 2004)
The arrested development of a permanent tooth as a sequela to a periradicular infection in a primary predecessor is a rare occurrence. A case is presented where temporary arrest of root development occurred in a premolar of a child with hypodontia and extensive caries.